The Effectiveness of Anticipation Guide and Visualization Strategies in Teaching Reading Comprehension to Students With High and Low Motivation - Sari, Fitriana Kartika; Anggani L, Dwi; Faridi, Abdurrachman (Universitas Negeri Semarang, 2020)
Teaching reading comprehension is not easy, the teacher must consider an appropriate strategy that can influence in the way of teaching-learning. The problem came from the Eight Grade students of SMPN 1 Kersana Brebes in the Academic year 2019/2020. The students lack motivation English subject because the teacher taught using conventional strategy which made them bored and could not achieve good score in English subject. The present study aims to explain how significant the students’ achievement taught by using anticipation guide and visualization strategies in teaching reading comprehension to students with high and low motivation. This study was a quasi-experimental design with a 2x2 factorial design conducted in eighth grade students at SMPN 1 Kersana, Brebes as the research participants. There are two experimental group involved. The students’ different level of motivation was taken as a factor that might influence the strategies. In collecting data, the writer used reading comprehension test to get students’ scores and questionnaires. The data was analyzed using ANOVA to answer the main hypotheses. Based on the analysis of the significance score was 0.000 which was lower than 0.05. It can be concluded that there was significance difference on the students’ achievement taught by anticipation guide and visualization for students with high and low motivation. This research is expected to give a contribution to give a contribution to English teaching learning such as giving appropriate strategy to teach reading comprehension.